Mean platelet volume as an indicator of severity of hypertensive retinopathy in hypertensive subjects - Yadav, Vishal; Jain, Pragya; Singhai, Abhishek; Jha, Rajesh Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Hypertensive retinopathy (HR) represents the ophthalmic findings of end-organ damage secondary to systemic arterial hypertension. Platelets play a crucial role in the pathogenesis of atherosclerotic complications, contributing to thrombus formation or apposition after plaque rupture. The aim of our study was to investigate whether Mean platelet volume (MPV) is associated with the severity of hypertensive retinopathy in hypertensive patients. Methods: This cross-sectional study was conducted in Department of Medicine of SAMC and PGI, Indore. Total 250 adult hypertensive patients (BP >140/90 mm Hg or taking antihypertensive drugs) recruited for the study. Results: Of the 250 subjects, 158 (63.2%) were male and 92 (36.8%) were female. Elevated MPV >11.5 femtoliter was observed in 84 cases (33.6%). There was statistically significant relationship between the grade of retinopathy and elevated MPV in hypertensive subjects. (r = 0.52, P <0.001). Conclusions: We described a relation between MPV and HR (probably first time in Indian patients). Measurement of MPV is easy to establish and therefore might serve as a valuable predictor of a worse outcome in microvascular complications.